Analisis Pengaruh Konflik Kerja, Stres Kerja, Komitmen Organisasi Dan Kompensasi Terhadap Kinerja Pegawai Pada Kantor Dinas Pekerjaan Umum Dan Penataan Ruang (PUPR) Kabupaten Alor (Studi Kasus Pada Kantor Dinas Pekerjaan Umum Dan Penataan Ruang Kabupaten - Illu, Steven Waang; Gorang, Alvonso Fanisius; Peny, Theresia Lounggina Luisa; Hermayanti, Hermayanti (Jurnal Ilmiah Wahana Pendidikan, 2023)
Performance is the result of work in quality and quantity achieved by an employee in carrying out his duties in accordance with the responsibilities given to him and in this study aims to determine the effect of work conflict, work stress, organizational commitment and compensation, this type of research is quantitative research with data collection techniques, namely observation, interviews, and documentation studies. This study used primary population data and the sample was employees at the Alor Regency Public Works and Spatial Planning Office which amounted to 58 employees. And the sampling technique in this study is saturated samples. The statistical method used in this study is multiple linear regression. The results of this study show that: Partially the work conflict variable has a significant value of 0.000 where this value is smaller than the alpha value of 0.05 so that the results of this study receive H1 which states that partial work conflict has a positive effect on employee performance at the Office of Public Works and Spatial Planning of Alor Regency. The partial variable of work stress has a significant value of 0.006 where this value is smaller than the alpha value of 0.05 so that the results of this study receive H2 which states that partial work stress has a positive effect on employee performance at the Office of Public Works and Spatial Planning of Alor Regency. The partial variable of organizational commitment has a significant value of 0.000 where this value is smaller than the alpha value of 0.05 or 5% so that the results of this study receive H3 which states that partial organizational commitment has a positive effect on employee performance at the Office of Public Works and Spatial Planning of Alor Regency. Partial compensation variable has a significant value of 0.001 where this value is smaller than the alpha value of 0.05 so that the results of this study receive H4 which states that partial compensation has a positive effect on employee performance at the Alor Regency Public Works and Spatial Planning Office. Simultaneously, work conflict variables, work stress, organizational commitment, and compensation have a significant value of 0.000, where this value is smaller than the alpha value, namely H5, which states that the variables of work conflict, work stress, organizational commitment, and compensation simultaneously have a positive effect on employee performance at the Alor Regency Public Works and Spatial Planning Office.